Sulabha-Janaka Samvada in Vyasa’s Mahabharata: Debating Meaning and Language Structures - Singh, Alka; Arora, Bhavya (IJLHE: International Journal of Language, Humanities, and Education, 2022)
The present paper offers an analytical study on the Sulabha-Janaka Samvada as one of the significant pieces of philosophical and religious instructions in the Shanti Parva of Vyasa’s Mahabharata. The dialogue that takes place between a male emperor and female recluse stands tall not only because it serves as an exploration of key feminine voices incessantly debating the ideas of Samkhya Philosophy and means to salvation(moksa) but also because it establishes Sulabha’s discourses as a rare occasion in the ambit of Sanskrit Literature. In this discourse, we find the idea of what constitutes a well-knit argument, proponents of a debate that defines meaning-making in the process of closely scrutinized and investigated language structure. This discourse between two polar personalities becomes a short philosophical dialogic treatise, amid hefty monologues such as the incessant instructions by Krishna in the Bhagavad Gita and Bheeshma in the Shanti Parva interspaced by many teachings of Vidura. Sulabha’s counter-arguments to Janaka are significant for it redefines the meaning and path to moksa, and in the process, expounds on what is proper speech, the correct usage of language and vocabulary and the purpose of doing so irrespective of the biases of class, gender, caste and educational elitism. The Sulabha-Janaka conversation has not received its due credit either in the Western or Eastern academic scholarship and scholarly attention has only been invested in the teachings of theGita, the ideas of dharma and many similar aspects. This short textual study provides a fresh perspective on philosophizing human need of meaning making and understanding the art of negotiating the engagement process of meaning associated with its structure. Keywords: Sulabha-JanakaSamvaad, female aesthetics, Samkhya Philosophy, language, meaning, structure, Vyasa’s Mahabharata,